2000
DOI: 10.1159/000016778
|View full text |Cite
|
Sign up to set email alerts
|

Capillarity, Fibre Types and Fibre Morphometry in Different Sampling Sites across and along the Tibialis anterior Muscle of the Rat

Abstract: Capillarity, fibre types, fibre cross-sectional areas and perimeters were studied along and across the rat tibialis anterior muscle. The muscle was sectioned at three different levels (proximal, equatorial and distal) choosing five sampling fields for measurements at each level (from anterior to posterior and lateral to medial zones). Significant differences were found in the percentage of fibre types and capillarity between different fields of the same muscle section. Slow oxidative fibres were confined to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Laughlin and Armstrong (1982) demonstrated that adrenergic vasoconstriction is greater in low-oxidative, fast-twitch skeletal muscle than in high-oxidative muscle at rest and during exercise. In animals, the proximal portion of the skeletal muscle contains a higher percentage of slow oxidative fibers than the distal portion (Torrella et al 2000;Wang and Kernell 2000). Johnson et al (1973) reported that muscle fiber type composition is similar in the medial and lateral heads of the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Laughlin and Armstrong (1982) demonstrated that adrenergic vasoconstriction is greater in low-oxidative, fast-twitch skeletal muscle than in high-oxidative muscle at rest and during exercise. In animals, the proximal portion of the skeletal muscle contains a higher percentage of slow oxidative fibers than the distal portion (Torrella et al 2000;Wang and Kernell 2000). Johnson et al (1973) reported that muscle fiber type composition is similar in the medial and lateral heads of the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Since rat TA (Torrella et al 2000) and DG (Green et al 1984) muscle Wbre is heterogeneous, several Welds or sample zones were selected from each muscle. The equatorial zone of the TA was analysed using Wve Welds from the cross-sectional area following the protocol described in Torrella et al (2000) as represented schematically in Fig.…”
Section: Morphofunctional Measurementsmentioning
confidence: 99%
“…The equatorial zone of the TA was analysed using Wve Welds from the cross-sectional area following the protocol described in Torrella et al (2000) as represented schematically in Fig. 2.…”
Section: Morphofunctional Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animal studies, the distal portion of skeletal muscle has a lower percentage of SO-type fibers than the proximal portion [8,9]. Regional differences in blood flow may reflect regional differences in the number of arterioles and/or capillaries, which may depend on the muscle fiber types [1].…”
mentioning
confidence: 99%